Changing Smoking Behavior of Staff at Dr. Zainoel Abidin Provincial General Hospital, Banda Aceh - Said Usman; Soekidjo Notoadmodjo; Kintoko Rochadi; Fikarwin Zuska (Hindawi Limited, 2014)
Smoking tobacco is a habit of individuals. Determinants of smoking behavior are multiple factors both within the individual and in the social environment around the individual. Staff smoking has been an undesirable phenomenon at Dr. Zainoel Abidin Provincial General Hospital in Banda Aceh. Health promotion efforts are a strategy that has resulted in behavioral changes with reductions in smoking by staff. This action research was designed to analyze changes in smoking behavior of hospital staff. The sample for this research was all 152 male staff who were smokers. The results of this research showed that Health Promotion Interventions (HPI) consisting of personal empowerment plus social support and advocacy to improve employee knowledge and attitudes influenced staff to stop or to significantly. HPI employed included counseling programs, distribution of antismoking leaflets, putting up antismoking posters, and installation of no smoking signs. These HPI proved effective to increase knowledge and create a positive attitude to nonsmoking that resulted in major reductions in smoking by staff when offsite and complete cessation of smoking whilst in the hospital. Continuous evaluation, monitoring, and strengthening of policies banning smoking should be maintained in all hospitals.